ANALISIS IMAM IBNU QUDAMAH TENTANG KEPEMILIKAN BAHAN GALIAN TAMBANG KONTINUITAS - Anwar Habibi Siregar; Hendra Gunawan (Institut agama islam negeri Padangsidimpuan, 2021)
This paper discusses about the concept of Imam Ibn Qudamah who has made important innovations in the ownership of mining minerals. It’s formulated in the concepts of al-ma'adin al-jariyah and al-ma'adin al-jamidah. the first part is included in the general ownership, while the second part is in the individual ownership. This research is a qualitative research (library research) that requires researchers to explore primary, secondary, and complementary sources according to research needs. The method used in the study is the exploratory-analytic-comparative method. This paper supports the opinion of Muhammad Baqir al-Sadr (2003) and Muhammad Sholahuddin (2007). According to them, if someone tries and works hard to find mining minerals, then he has the right to own it as private property. however, if the mining material has a large quantity of reserves, it is included in the category of public or common property and must be managed by the government (state).